Associations between internal exposure levels of persistent organic pollutants in adipose tissue and deep infiltrating endometriosis with or without concurrent ovarian endometrioma. (November 2017) - Ploteau, Stéphane; Cano-Sancho, German; Volteau, Christelle; Legrand, Arnaud; Vénisseau, Anaïs; Vacher, Vincent; Marchand, Philippe; Le Bizec, Bruno; Antignac, Jean-Philippe
Abstract: Endometriosis is a gynaecological disease characterized by the presence of ectopic endometrial tissue. Histologically, it appears as different sub-types, being peritoneal endometriosis, ovarian endometrioma (OvE) and deep infiltrating endometriosis (DIE), which are of major relevance due to their varying clinical presentations. A number of persistent organic pollutants (POPs) have been associated with the onset of endometriosis, yet the overall set of existing studies remains fairly divergent. In this preliminary case-control study we aimed to assess the potential associations between the internal exposure to POPs and the presence of DIE with or without concurrent OvE. Adipose tissue and serum samples were collected from surgically confirmed cases (n = 55) and controls (n = 44) enrolled during 2013 and 2015 in Pays de la Loire, France. Targeted pollutants (76 historical or more emerging POPs including dioxins, polychlorobiphenyls (PCB), polybrominated diphenyl ethers (PBDEs), polybrominated biphenyls (PBBs), hexabromocyclododecanes (HBCDs) and organochlorine pesticides (OCPs) were quantified by chromatography coupled to mass spectrometry. Odds ratios (ORs) and 95% confidence intervals (CI) were estimated from unconditional logistic regression adjusted for known confounding variables. The results showed significant associations between DIE and adipose tissue levels of 1.2.3.7.8 – PeCDD, OCDF, PCB 105, 114, 118 and 123, PBDE 183, PBB 153, and several OCPs including trans‑nonachlor, cis‑heptachlor epoxide, dieldrin, β-hexachlorocyclohexane and hexachlorobenzene. The largest associations were observed for OCDF followed by cis‑heptachlor epoxide, exhibiting adjusted ORs (95% CI) of 5.42 (2.73–12.85) and 5.36 (2.44–14.84) per 1-SD increase, respectively. The stratified analysis comparing both disease sub-types suggested that adipose tissue exposure markers may be more associated with DIE concurrent with OvE, however these results need to be confirmed in a larger population. Highlights: Deep infiltrating endometriosis was associated with exposure to several POPs. Associations were largest for cases with concurrent ovarian endometrioma. Adipose tissue exposure markers were more associated than serum biomarkers.